2009
DOI: 10.1152/ajprenal.90757.2008
|View full text |Cite
|
Sign up to set email alerts
|

Increased hypoxia and reduced renal tubular response to furosemide detected by BOLD magnetic resonance imaging in swine renovascular hypertension

Abstract: . Increased hypoxia and reduced renal tubular response to furosemide detected by BOLD magnetic resonance imaging in swine renovascular hypertension. Am J Physiol Renal Physiol 297: F981-F986, 2009. First published July 29, 2009 doi:10.1152/ajprenal.90757.2008.-Oxygen consumption beyond the proximal tubule is mainly determined by active solute reabsorption, especially in the thick ascending limb of the Loop of Henle. Furosemide-induced suppression of oxygen consumption (FSOC) involves inhibition of sodium tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
5
36
0
1
Order By: Relevance
“…ROIs = 1-7. with either contralateral kidneys or kidneys with EH. These observations extend the results of Gomez et al (28), who reported reduced furosemide-suppressible oxygen consumption in the kidneys beyond the stenosis with reduced GFR in a swine model. In this study, we further compared BOLD MR images obtained from multiple axial sections from the same kidneys.…”
Section: Genitourinary Imaging: Human Renovascular Disease Saad Et Alsupporting
confidence: 91%
“…ROIs = 1-7. with either contralateral kidneys or kidneys with EH. These observations extend the results of Gomez et al (28), who reported reduced furosemide-suppressible oxygen consumption in the kidneys beyond the stenosis with reduced GFR in a swine model. In this study, we further compared BOLD MR images obtained from multiple axial sections from the same kidneys.…”
Section: Genitourinary Imaging: Human Renovascular Disease Saad Et Alsupporting
confidence: 91%
“…Specifically, the oxygen tension of the kidney cortex and medulla has been shown to be approximately 10 mm Hg lower than normal in spontaneously hypertensive rats and other models of hypertension as well as in hypertensive patients. 15,89,[144][145][146] The role of hypertension in the progression of CKD was first described in 1914 by Volhard and Fahr. 13 Subsequently, it was appreciated that hypertension predisposes to kidney failure by inducing renal hypoxia.…”
Section: Hypertensionmentioning
confidence: 99%
“…These investigators concluded that the response to furosemide can be used to distinguish between viable parenchyma (baseline hypoxia with amelioration after furosemide) and nonviable renal tissue (baseline hyperoxia without response to furosemide). Similarly, Gomez et al 72 utilized BOLD MRI in a swine model of renal artery stenosis and found that the ability of furosemide to suppress oxygen consumption in stenotic kidneys with reduced GFR was blunted compared with stenotic kidneys with preserved GFR. Consistent with the observations of Textor et al, 27 Chrysochou et al 73 found that in humans with atherosclerotic renal artery stenosis, stenotic kidneys with renal hypoxia detected by BOLD MRI were more likely to show a favorable renal functional response to revascularization.…”
Section: Neugarten and Golestanehmentioning
confidence: 99%